2021
DOI: 10.1016/j.ijscr.2021.106472
|View full text |Cite|
|
Sign up to set email alerts
|

Pneumothorax as a rare complication of peripherally inserted central catheter (PICC) in neonates: A case report study

Abstract: Introduction and importance The Peripherally Inserted Central Catheter (PICC) placement is associated with complications such as deep vein thrombosis, phlebitis, air embolism, infection, and superior vena cava syndrome. The aim of this study is to report pneumothorax as a rare complication of PICC insertion in a newborn. Case presentation The present case report is of a 32-week- and 4-day-old female fetus who was born at Mahzad Obstetrics and Gynecology Hospital, Urmia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Punctures that include upper extremity block, subclavian or intrajugular venous puncture catheterization, are less successful and have complications[ 24 ]. Goli et al [ 25 ] reported a 32-wk premature infant who underwent peripherally inserted central catheter (PICC) catheterization at 4 d of birth. After the PICC was placed for 2 h, the baby’s oxygen saturation decreased to 45%, and the baby developed tachycardia and shortness of breath.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Punctures that include upper extremity block, subclavian or intrajugular venous puncture catheterization, are less successful and have complications[ 24 ]. Goli et al [ 25 ] reported a 32-wk premature infant who underwent peripherally inserted central catheter (PICC) catheterization at 4 d of birth. After the PICC was placed for 2 h, the baby’s oxygen saturation decreased to 45%, and the baby developed tachycardia and shortness of breath.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Infants, especially premature newborns, need an environment that is equipped with advanced medical technology and specialized nursing care in order to survive, but unfortunately, this environment inadvertently endangers the baby's organs [3] . In the NICU, the insertion of an intravenous catheter is a common procedure for venipuncture, blood pressure measurement, and administering intravenous fluids, or intravenous nutrition and medication [4] . Approximately 95% of peripheral venous catheters are removed due to complications such as infections, phlebitis, vessel rupture and drug leaks or serum.…”
Section: Introductionmentioning
confidence: 99%
“…PICCs are usually inserted into large peripheral veins (to deliver drugs and nutrients over a long period of time, because a large vein can tolerate a IV catheter longer than a small vein) of the arm, such as the cephalic vein or the basilic vein near the elbow, and guided toward the superior vena cava ( Fig. 1 ) 5 . Since the most appropriate and convenient place for vascular access to insert the PICC is the basal and cephalic veins in the right arm of the infant, so it is recommended that infants who are preterm and may be hospitalized for a long time save the right arm.…”
mentioning
confidence: 99%
“…Considering the long length of stay of preterm infants in the neonatal intensive care unit and the poor stability of peripheral venous access, another means of venous access is needed [4] . Indeed, venous access is an important dimension of treatment in neonates [5] . The peripheral central catheter (PICC) is a long, thin catheter made of soft, flexible silicone or polyurethane [6] .…”
mentioning
confidence: 99%